DEVELOPMENT OF MICROSTRIP ANTENNA WITH RECONFIGURABLE POLARIZATION FOR EMI MEASUREMENT AND WIRELESS COMMUNICATION - Cahyaningsih, Elmi
In wireless communication systems, antennas with reconfigurable polarization are required to minimize multipath fading losses and enhance signal transmission performance by minimizing polarization mismatches and interference with other systems. The polarization of electromagnetic waves emitted by the antenna may experience depolarization during propagation, resulting in Polarization Loss Factor (PLF) and reducing the received power intensity. Reconfigurable polarization microstrip antennas are proposed to address this issue. This research involves the design, simulation, and realization of microstrip antennas with reconfigurable polarization. These antennas operate at frequencies of 915 MHz and 1,575 GHz. Furthermore, the antenna is applied as a sensor to observe the impact of polarization on the measurement results of radiated emissions (RE) from the Equipment Under Test (EUT). Simulation and realization results show that the designed antennas have the capability to switch between circular and linear polarizations. In the RE measurements, microstrip antennas with circular polarization design produce lower electric field strength levels than antennas with linear polarization design in vertical polarization mode and higher levels than antennas with linear polarization design in horizontal polarization mode.